The Struggle of a Geisha in Maintaining Her Pride as Seen in Arthur Golden’s Memoirs of a Geisha - Handriyani, Ramiyati; Astuti, Amelia Yuli (Jurnal Ilmiah Langue and Parole, 2019)
This thesis is entitled "The Struggle of Geisha in Maintaining Her Pride as seen in Arthur Golden's Memoirs of a Geisha" seen from the perspective of structuralism. This research is limited on basic ideas that relate to the observation into three questions as follow: (1) how is geisha’s life before World War II (2) how was the geisha struggle after World War II, and (3) how is geisha maintaining her pride before and after second world war. The objectives of this research were (1) to analyze Sayuri’s life before World War II (2) to explain Sayuri's life after World War II, and (3) to study and explain the types of struggles in maintaining her pride by Sayuri as the main female character , to oppose and think of Sayuri's struggle to fight exploitation and significant meaning, and to find out and explain the depiction of Sayuri's struggle. The theory used is from Gough and Gautam about the structural analysis used to answer the purpose of this research. For the method of data analysis, the author uses systematic procedures with novel understanding and structural theory. Data collection techniques use documentation techniques in finding data that is relevant to the subject of analysis. The object of this research is a novel entitled Memoirs of a Geisha written by Arthur Golden in 1997 and the data are sentences related to the struggle of a woman found in the novel. Sayuri as the main female character in the novel represents women in general who can gain their independence and have a smart and brave attitude to take the important decisions in their life.